City in Dragon Circle: Study of the History of Pagoda and Its Deployment in Manado, 1819 - 2018 - Ivan Robert Bernadus Kaunang (Department of History, Faculty of Humanities, Diponegoro University, 2020)
This study discusses the history of the pagoda formation and its distribution along with the presence of Chinese existence in Manado. This study also discusses the factors and the impact of the pagoda in Manado. The first pagoda in Manado was beginning to exist in 1819, and in a fairly long period until 2018, the development and distribution were very slow despite the presence of Chinese in this area since the 17th century. This study was carried out using historical methods and analysis. The data obtained were processed using a qualitative descriptive approach. The results of the study show that the presence of the pagoda together with the initial settlement of Chinese people brought by the Dutch VOC was aimed to build the fort of Fort Amsterdam. Although it impressed by the slow erection and distribution of pagodas in Manado, the causal factors and the impact are interesting in relation to interfaith, interethnic relations, urban expansion, religious space contestation, opening wider economic access and become tourism destinations.